Application of Kweau Accounting in Weddings of the Lani Tribe of Wamena Papua - Degei, Yoni; Rusmita, Sari; Yunita, Khristina (Technium Business and Management, 2024)
Recording transactions for purchasing pig livestock assets as a marriage medium for the Lani tribal community in Wamena. These documents or records of transactions or events are the guidance of both parties in the marriage process. The aim of this research is to discuss identifying, measuring, communicating, presenting and disclosing kweau accounting in the marriage process of the Lani Wamena tribal community. This research used qualitative methods from the results of interviews and observations. The researcher concluded that the identification of notes needs to be adjusted to the fair value or transaction price when pig assets are purchased on the market, so that the process of measuring, communicating, presenting and disclosing in accounting is realized. The researcher also provides an overview of purchase measurement records, general journals and presentation of accounting financial reports so that they can be used at subsequent wedding events.